Auditor-client alignment through competitive priorities – evidence from Italy. (1st January 2013) - Imoniana, Joshua Onome; Bianchi, Massimo; Tampieri, Laura
This study investigates the alignment of the big- four independent audit firms and their respective clients in Italian environment. Investigating auditor-client alignment through competitive priorities therefore, tends to bridge the gap between academia and practice. It is interventionist in nature and tends to produce thought leadership information to improve business decision-making, interpret complex questions affecting both sides and finally establish a fact base for auditor-auditee relationship. It is exploratory in nature and supported with the question: if the independent auditor is aligned with the client based on competitive priorities? Selecting a purposeful sample of eight independent auditors and their respective eight clients, data was gathered face-to-face and have been treated through: content analysis of qualitative data automated through NVivo and descriptive analysis of some structured questions. Finally, based on findings, we conclude for no association of competitive priorities more valued by the auditors aligned strategically with the clients in Italian environment.